Pengaruh Pemberian Pupuk Kandang Burung Puyuh dan Pupuk Kandang Sapi Terhadap Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L.) - Siska Putri Utami; Akhmad Gazali; Akhmad Rizali (Agroekotek View, 2021)
Lettuce (Lactuca sativa L.) is a widely cultivated vegetable crop and is also a horticultural commodity that has good prospects and commercials. So that fertilization with organic fertilizers is needed to get optimum results. Quail manure and cow manure are thrown away, causing environmental pollution, especially the smell of quail droppings and cow dung. Is studi determineof fertilizer quail manure and cow manure ongrowth and yield of lettuce, with determine the best dose on lettuce development and yield. This attempt was implemented at the Agroecotechnology trial Garden, Faculty of Agriculture, Lambung Mangkurat Universit, Banjarbaru, South Kalimantan from January to March 2020. Using a one-factor plan random group (PRG) with four treatments and six replicates to produce 24 experiments. Observation parameters in the study were lettuce plant tall, leaf width, number of leaves and wet weight of lettuce plants. The application of quail manure and cow manure had a very significant effect on plant tall, number of leaves, leaf width at 35 DAS, and wet weight of lettuce plants. The best doses of quail manure and cow manure in influencing the growth of lettuce were found in S1 treatment at a dose of 50 g / polybag.